Estimation of rest periods for newly constructed/reconstructed pavements - Ahmed, Anwaar; Saeed, Tariq U.; Labi, Samuel (Transport, 2016)
Newly-constructed and reconstructed highway pavements under the effect of traffic loading and climatic severity deteriorate progressively and need preservation intervention after a certain number of years following their construction. In the literature, the term ‘rest period’ has been used to refer to the number of years that elapse between the construction completion to the application of first major repair activity. The rest period is a critical piece of information that agencies use to not only plan and budget for the first major repair activity but also to develop more confidently, their life-cycle activity schedules for life cycle costing, work programming, and long-term plans. However, the literature lacks established procedures for predicting rest periods on the basis of pavement performance thresholds. In the absence of such resources, highway agencies rely mostly on expert opinion for establishing the rest periods for their pavement sections. In addressing this issue, this paper presents a statistical methodology for establishing the rest periods for newly-constructed or reconstructed pavements. The methodology was demonstrated using empirical data from in-service pavements in a Midwestern State in the US. The paper’s results show that the rest periods of newlyconstructed and reconstructed highway pavements are significantly influenced by their functional class, surface material type, traffic loading level, and climate severity.